Predictive Factors for Survival in Children Receiving Liver Transplants for Wilson's Disease: A Cohort Study Using European Liver Transplant Registry Data. Issue 9 (24th September 2018) - Pfister, Eva‐Doreen; Karch, André; Adam, René; Polak, Wojciech G.; Karam, Vincent; Mirza, Darius; O'Grady, John; Klempnauer, Jürgen; Reding, Raymond; Kalicinski, Piotr; Coker, Ahmet; Trunecka, Pavel; et al.
Abstract : Liver transplantation (LT) is a rescue therapy for life‐threatening complications of Wilson's disease (WD). However, data on the outcome of WD patients after LT are scarce. The aim of our study was to analyze a large pediatric WD cohort with the aim of investigating the longterm outcome of pediatric WD patients after LT and to identify predictive factors for patient and transplant survival. This is a retrospective cohort study using data of all children (<18 years) transplanted for WD enrolled in the European Liver Transplant Registry from January 1968 until December 2013. In total, 338 patients (57.6% female) transplanted at 80 different European centers (1‐26 patients per center) were included in this study. The median age at transplantation was 14.0 years (interquartile range [IQR], 11.2‐16.1 years); patients were followed up for a median of 5.4 years (IQR, 1.0‐10.9 years) after LT. Overall patient survival rates were high with 87% (1‐year survival), 84% (5‐year survival), and 81% (10‐year survival); survival rates increased considerably with the calendar year ( P < 0.001). Early age at LT, living donation, and histidine tryptophan ketoglutarate preservation liquid were identified as risk factors for poor patient survival in the multivariate analysis. LT is an excellent treatment option for pediatric patients with WD and associated end‐stage liver disease. Longterm outcome in these patients is similar to other pediatric causes for LT. Overall patient and graft survival rates improved considerably over the last decades. To improve future research in the field, the vast variability of allocation strategies should be harmonized and a generally accepted definition or discrimination of acute versus chronic WD needs to be found.